The man who shocked the world : the life and legacy of Stanley Milgram - Blass, Thomas (New York : Basic Books, 2004)
"The creator of the famous "Obedience Experiments," carried out at Yale in the 1960s, and originator of the "six degrees of separation" concept, Stanley Milgram was one of the most innovative scientists of our time. In this biography - the first in-depth portrait of Milgram - Thomas Blass captures the colorful personality and pioneering work of a man who profoundly altered the way we think about human nature."--Jacket.
The neighborhood with no name -- Making the grade at Harvard -- Norway and France -- From the "princetitute" to Yale -- Obedience: the experience -- Obedience: the experiment -- Aftershocks -- Return to academic Eden -- City psychology -- Center stage -- Vexations, cyranoids, and the declining years -- Milgram's legacy.
Includes bibliographical references (pages 305-347) and index.
Keywords: Milgram, Stanley; Milgram, Stanley; Milgram, Stanley; Milgram, Stanley; Milgram, Stanley; Social psychologists -- United States -- Biography; Authority; Obedience; Social psychology; Social psychology -- Experiments; Psychology, Social; Social Conformity; Behavioral Research -- history; Behavioral Research -- ethics; Psychosociologues -- Biographies; Psychologie sociale; Psychologie sociale; Authority; Obedience; Social psychologists; Social psychology; Social psychology -- Experiments; United States; Sociale psychologie; Experimenten; Milgram-Experiment; Sozialpsychologie; Biography; Biographies; Biography; Biographies; Biographies